1700 nm and 1800 nm band tunable thulium doped mode-locked fiber lasers - Emami S.D.; Dashtabi M.M.; Lee H.J.; Arabanian A.S.; Rashid H.A.A. (Nature Publishing Group, 2023)
This paper presents short wavelength operation of tunable thulium-doped mode-locked lasers with sweep ranges of 1702 to 1764 nm and 1788 to 1831 nm. This operation is realized by a combination of the partial amplified spontaneous emission suppression method, the bidirectional pumping mechanism and the nonlinear polarization rotation (NPR) technique. Lasing at emission bands lower than the 1800 nm wavelength in thulium-doped fiber lasers is achieved using mode confinement loss in a specially designed photonic crystal fiber (PCF). The enlargement of the first outer ring air holes around the core region of the PCF attenuates emissions above the cut-off wavelength and dominates the active region. This amplified spontaneous emission (ASE) suppression using our presented PCF is applied to a mode-locked laser cavity and is demonstrated to be a simple and compact solution to widely tunable all-fiber lasers. 2017 The Author(s).